2024
DOI: 10.1021/acs.joc.3c02406
|View full text |Cite
|
Sign up to set email alerts
|

Three-Component Reaction between 3-Acetylcoumarins, Amines, and Elemental Sulfur: A Designed Approach to 3-Amino-4H-thieno[3,2-c]coumarins

Behnaz Farajpour,
Roujin Heydarzadeh,
Faiq H. S. Hussain
et al.

Abstract: In this work, a series of novel 3-amino-4Hthieno[3,2-c]coumarins were designed and synthesized by a onepot, catalyst-free, and three-component reaction of 3-acetylcoumarins with amines and elemental sulfur. Readily available starting materials, simple heating conditions, facile installation of a sulfur atom into the molecule using S 8 as a sulfur source, acceptable functional group tolerance, and synthetically useful yields are some highlighted benefits of this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 73 publications
0
1
0
Order By: Relevance
“…Yavari et al reported the synthesis of spiropyrrolizidine-linked rhodanines through [3 + 2] cycloaddition reactions of azomethine ylides, prepared in situ from l -proline and acetylenic esters and alkylidene rhodanines . As a part of our ongoing studies directed toward developing practical and novel synthetic protocols for heterocycles, we decided to employ alkylidene rhodanines for the synthesis of novel rhodanine-based molecules …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yavari et al reported the synthesis of spiropyrrolizidine-linked rhodanines through [3 + 2] cycloaddition reactions of azomethine ylides, prepared in situ from l -proline and acetylenic esters and alkylidene rhodanines . As a part of our ongoing studies directed toward developing practical and novel synthetic protocols for heterocycles, we decided to employ alkylidene rhodanines for the synthesis of novel rhodanine-based molecules …”
Section: Introductionmentioning
confidence: 99%
“… 9 As a part of our ongoing studies directed toward developing practical and novel synthetic protocols for heterocycles, we decided to employ alkylidene rhodanines for the synthesis of novel rhodanine-based molecules. 10 …”
Section: Introductionmentioning
confidence: 99%